2021
DOI: 10.1007/s11661-021-06475-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alloying to Effect an Equiaxed Microstructure in Additive Manufacturing and Subsequent Heat Treatment of High-Strength Titanium Alloys

Abstract: This paper addresses the use of alloying additions to titanium alloys for additive manufacturing (AM) with the specific objective of producing equiaxed microstructures. The additions are among those that increase freezing ranges such that significant solutal undercooling results when combined with the rapid cooling rates associated with AM, and so be effective in inducing a columnar-to-equiaxed transition (CET). Firstly, computational thermodynamics has been used to provide a simple graphical means of predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Strongly partitioning elements are segregated into the liquid, slowing the growth of the columnar front while also promoting nucleation by increasing the constitutional undercooling [15]. Elements which have previously been investigated for this purpose in Ti alloys fabricated using AM technologies include Be [16], B [17], La [18], Fe or Ni [19]. Y additions to Ti-64 have resulted in an order of magnitude refinement of the β grain size, attributed to both the solutal effect of Y on growth restriction as well as the potential heterogeneous nucleation of β on yttria during solidification [20].…”
Section: Introductionmentioning
confidence: 99%
“…Strongly partitioning elements are segregated into the liquid, slowing the growth of the columnar front while also promoting nucleation by increasing the constitutional undercooling [15]. Elements which have previously been investigated for this purpose in Ti alloys fabricated using AM technologies include Be [16], B [17], La [18], Fe or Ni [19]. Y additions to Ti-64 have resulted in an order of magnitude refinement of the β grain size, attributed to both the solutal effect of Y on growth restriction as well as the potential heterogeneous nucleation of β on yttria during solidification [20].…”
Section: Introductionmentioning
confidence: 99%
“…and anisotropy. Zhang et al [16] used Cu additions, but similar effects have been demonstrated using Fe, [17][18][19][20] Ni, [19,21,22] and Co. [23] The transition metals mentioned before belong to the group of β-eutectoid-forming elements when added to Ti. [1,24] Upon heat treatment below the eutectoid temperature, the β-phase decomposes into α phase and various intermetallic phases with different stoichiometry and crystallography.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, several works explored the introduction of transition metals into titanium alloys. [16][17][18][19][20][21][22][23] Zhang et al [16] suggested that alloying elements with pronounced partitioning behavior into the remaining melt during solidification and a steep liquidus curve provide a high growth restriction factor, resulting in grain refinement and a strong reduction of texture DOI: 10.1002/adem.202300177 Titanium alloys gain increasing importance in industry due to the expansion of advanced manufacturing technologies such as additive manufacturing. Conventional titanium alloys processed by such technologies suffer from formation of large primary grains and anisotropy of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations